Clinical psychology and the philosophy of science - O'Donohue, William (Springer International Publishing, 2013)
Is psychology really a science? If it is not a science as physics or chemistry is, can it be a science of another kind? Does the discipline play by valid scientific rules? Can we prove this? These questions have been debated for over a century, and clear-cut answers have yet to find consensus. Proposing provocative new directions in critical thinking, Clinical Psychology and the Philosophy of Science asks readers to revisit what they know--and especially how they came to know it. Offering a concise guide to the central concepts philosophy uses to make sense of science, this readable treatise persuades philosophers of science to look critically at the foundational problems of psychology, and clinicians to re-examine the theories and assumptions that fuel their approaches to their work. The author makes a robust case for multiple viewpoints as not only a necessity, but also a source of strength befitting living schools of thought. The book argues that the ongoing tensions between psychology and philosophy benefit both sides as it:  Identifies the major methods of philosophical inquiry. Sets out key questions in the philosophy of science of relevance to psychology. Explains the contemporary role of epistemology. Analyzes the impact on psychological inquiry of Popper, Kuhn, and their critics. Dissects Skinner's behavioral theory of science. Considers philosophical problems in the APA's code of ethics. For professionals in both disciplines, Clinical Psychology and the Philosophy of Science is an elegant vehicle for their intimately related fields to meet each other halfway, and a springboard for the continued evolution of both.